2021
DOI: 10.3390/jof7090763
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of the Phenolic Compounds Ellagic Acid (EA) and Caffeic Acid Phenethyl Ester (CAPE) against Drug-Resistant Candida auris

Abstract: Candida auris is an emerging healthcare-associated fungal pathogen that has become a serious global health threat. Current treatment options are limited due to drug resistance. New therapeutic strategies are required to target this organism and its pathogenicity. Plant polyphenols are structurally diverse compounds that present a vast range of biological properties. In the present study, plant-derived molecules ellagic acid (EA) and caffeic acid phenethyl ester (CAPE) were investigated for their antifungal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…Another study performed by Possamai Rossatto and coworkers showed similar results, where CAPE was also able to inhibit the growth of C. auris with MIC values ranging from 1 to 64 µg/mL. Furthermore, CAPE was able to inhibit the biofilm formation and phospholipase production of C. auris [ 30 ]. Our findings also showed the ability of CAPE to enter the cells of Candida spp rapidly.…”
Section: Discussionmentioning
confidence: 74%
“…Another study performed by Possamai Rossatto and coworkers showed similar results, where CAPE was also able to inhibit the growth of C. auris with MIC values ranging from 1 to 64 µg/mL. Furthermore, CAPE was able to inhibit the biofilm formation and phospholipase production of C. auris [ 30 ]. Our findings also showed the ability of CAPE to enter the cells of Candida spp rapidly.…”
Section: Discussionmentioning
confidence: 74%
“…Previous results suggest that ellagic and gallic acids could be natural antifungal agents [52,53]. Ellagic acid had a broad spectrum of antifungal activity against two fungal Candida strains, with MICs between 25.0 and 75.0 µg/mL and 0.125 to 0.25 µg/mL against C. auris strains [54]. Meanwhile, Li et al [53] recorded antifungal MICs of gallic acid against three Candida strains ranging between 12.5 and 100.0 µg/mL.…”
Section: Discussionmentioning
confidence: 96%
“…The biofilm extracellular matrix is a second major contributor to antifungal drug resistance in C. albicans biofilms. The matrix acts as both a physical barrier to drug penetration and as a stabilizer of the overall architecture of the biofilms ( Nett et al, 2007 ; Nobile and Johnson, 2015 ), isolating antifungal molecules and preventing them from penetrating deeper into the biofilm ( Pierce et al, 2013 ; Possamai Rossatto et al, 2021 ). A third important resistance property is the biofilm-regulated efflux pumps.…”
Section: Discussionmentioning
confidence: 99%